Assessing the Oxidative Stability of Anion Exchange Membranes in Oxygen Saturated Aqueous Alkaline Solutions - Arges, Christopher G.; Ramani, Vijay; Wang, Zhongyang; Ouimet, Ryan J. (Frontiers in Energy Research, 2022)
While anion exchange membrane water electrolyzers show promise as a source of green hydrogen using low-temperatures and non-platinum group metal catalysts, many concerns must be addressed. A primary challenge for the development of high-performance anion exchange membrane water electrolyzers is the fabrication of a stable membrane that will be able to survive long-term stability test while maintaining high anion conductivity, which is a necessity for a durable water electrolyzer. This method will present a standardized protocol that can be used by researchers to assess the quality of their AEM materials and be able to provide insight into how materials may be degrading and how to improve the quality of AEMs. Using Mohr or Volhard titration to measure ion-exchange capacity, EIS to determine the ionic conductivity, NMR and FTIR to understand the extent of membrane degradation over time, and mechanical analyzers to determine the strength of their AEMs, this standardized protocol will guide researchers to determining and improving upon the long-term durability and performance of their AEM materials.